Préférences du consommateur mostaganémois vis-à-vis du Camembert - AFFER, Mohammed Imad Eddine (My University, 2021)
This work was carried out in order to know the characteristics and the most important consumption behaviors of the citizen and in particular of the consumer vis-à-vis one of the milk derivatives, specifically, Camembert. We have presented an overview on the current relative knowledge of Camembert, but passing by certain generalities of cheese as well as of milk its raw material of manufacture. We also studied consumer behavior towards Camembert. We have reserved a good part to demonstrate how a questionnaire survey is done and what a questionnaire consists of and its different forms.
Keywords: cheese, camembert, survey, questionnaire.